Microbial and biochemical mechanisms underlying greenhouse gas mitigation in agriculture - Yang, Seongmin (My University, 2026)
Greenhouse gases (GHGs) such as carbon dioxide (CO₂), nitrous oxide (N₂O), and methane (CH₄) play a crucial role in regulating Earth’s climate by trapping heat in the atmosphere. While carbon dioxide is the most abundant anthropogenic GHG, N₂O and CH₄ contribute disproportionately to global warming due to their much higher global warming potential, approximately 298 and 25 times greater than CO₂, respectively. N₂O and CH₄ are particularly concerned due to their persistence in the atmosphere. Natural processes and human activities both contribute to the production of N₂O and CH₄. Agricultural activities are the predominant source, responsible for over two-thirds of global anthropogenic N₂O emissions and one-third of total CH₄ emissions. In these agricultural systems, microbial processes are fundamental to the production and mitigation of both N₂O and CH₄. To elucidate microbial mechanisms regulating GHG fluxes in agricultural systems, this dissertation presents two complementary studies: one focusing on mitigating N₂O emissions during forage conservation, and the other examining the role of biological nitrification inhibition (BNI) in controlling CH₄ oxidation. Building on the recognition that anaerobic forage conservation may serve as an unrecognized source of N₂O, I conducted an extensive investigation using three major silage crops in the U.S.—maize, alfalfa, and sorghum. The total N₂O emission from these silage processes was quantified and emission potential was calculated with USDA National Agriculture Statistics Services annual silage production report, revealing that silage ranks as the third largest source of anthropogenic N₂O emissions in the U.S. Through chemical and molecular analyses, denitrifying bacteria were identified as the primary contributors to these emissions. Subsequently, a chemical combination was developed using chlorate—a specific inhibitor of nitrate reductase— mitigating N₂O emissions from silage up to 99%, offering a practical solution to significantly reduce GHG emissions in agriculture. The second part of this dissertation examines a novel phenomenon with significant environmental implications. Plant–microbe interactions in the rhizosphere strongly influence nitrogen cycling and GHG emissions. BNI through which plants release natural compounds that suppress nitrification, offers a sustainable alternative to synthetic inhibitors. However, the broader impacts of BNI on other microbial processes remain unclear. In particular, CH₄ oxidation by methanotrophs—the only biological sink for atmospheric CH₄—may be affected because the key enzymes involved in nitrification and methanotrophy share similar catalytic mechanisms. This effect could be significant in paddy environments like wetlands and rice fields, which are major contributors to global GHG emissions. To investigate this interaction, a multi-scale experimental approach was undertaken. Soil column experiments with BNI-producing plants demonstrated that BNI compounds reduced CH₄ oxidation activity and altered methanotrophic community structures. Pure culture experiments confirmed the direct inhibitory effects of specific BNI compounds on methanotrophs. These findings provide the first multi-lines of evidence that BNI can adversely affect methanotrophy, suggesting that while BNI reduces nitrification and associated N₂O emissions, it may unintentionally suppress CH₄ oxidation, potentially increasing CH₄ emissions. This novel discovery underscores the need for a balanced assessment of BNI's environmental impacts. Understanding BNI's dual effects is essential for developing sustainable agricultural practices that mitigate GHG emissions without unintended consequences. Collectively, these two studies advance our understanding of how nitrogen and carbon management practices influence GHG emissions in agricultural systems, providing valuable insights for developing more sustainable and climate-resilient agricultural strategies.
Keywords: Nitrous oxide; Forages; Denitrification; Methane; Methanotrophs; Biological nitrification inhibition